Empowering Students in Health Information Management through SIMRS to Enhance Community Health Education - Satrio Bhagas Yudhanto; Mirza Aulia; Devid Leonard (Sustainable Applied Modification Evidence Community (SAMEC), 2025)
The utilization of information technology in healthcare services is increasingly crucial, particularly in managing patient data and information through the Hospital Management Information System (SIMRS). Students of the Medical Records and Health Information Program need to be equipped with technical skills in using SIMRS as well as the ability to transform data into educational content for the community. Purpose: This community service activity aimed to enhance students’ competencies in SIMRS operations and encourage the use of data to support evidence-based health promotion. Methods: The program targeted 25 fourth-semester students who participated in participatory training and hands-on practice over two days. Evaluation was conducted through pre- and post-tests, direct observation during practice sessions, and assessment of the educational products created. Results: all   participants were able to operate SIMRS independently and develop educational media based on medical record data. Implications: This activity also improved students' analytical thinking and visual communication skills. Conclusion: The program demonstrates that hands-on SIMRS training effectively prepares students to become professionals who are adaptive to digital transformation in healthcare and capable of contributing to community-based health education.